Politics and society in the contemporary Middle East / edited by - "Angrist, Michele Penner. (ed.)" (New Delhi, 2012)
This cutting-edge, and at the same time lively and accessible, examination of the domestic politics of the Middle East has been carefully designed to meet the needs of the university classroom. Eight thematic chapters introduce the subject and explore the region-wide dynamics of governments and oppositions, international politics, political economy, civil society, religion and politics, identity politics, and gender and family issues. These themes are then systematically explored with regard to Algeria, Egypt, Iran, Iraq, Israel, Jordan, Kuwait, the Palestinian Authority, Saudi Arabia, Syria, Turkey, and the UAE. The result is an insightful overview and analysis that both provides a wealth of information and encourages comparative, critical thinking by students at all levels.
Keywords: Middle East-Politics and government